2017
DOI: 10.20892/j.issn.2095-3941.2017.0020
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of vitamin D receptor (VDR) expression in cutaneous melanoma tissues and four VDR gene polymorphisms

Abstract: Objective: Vitamin D receptor (VDR) mediates vitamin D activity. We examined whether VDR expression in excised melanoma tissues is associated with VDR gene (VDR) polymorphisms. Methods: We evaluated VDR protein expression (by monoclonal antibody immunostaining), melanoma characteristics, and carriage of VDR-FokI-rs2228570 (C>T),VDR-BsmI-rs1544410 (G>A),VDR-ApaI-rs7975232 (T>G), andVDR-TaqI-rs731236 (T>C) polymorphisms (by restriction fragment length polymorphism). Absence or presence of restriction site was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
2
12
1
Order By: Relevance
“…Of note is that its decreased expression correlates with advanced melanoma staging, progression and decreased overall patient survival and disease-free survival time [ 45 , 46 ]. Accordingly, VDR polymorphism [ 41 , 42 , 72 ] and decreased levels of 25(OH)D 3 in the serum [ 33 , 86 ] positively correlate with melanoma prevalence and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note is that its decreased expression correlates with advanced melanoma staging, progression and decreased overall patient survival and disease-free survival time [ 45 , 46 ]. Accordingly, VDR polymorphism [ 41 , 42 , 72 ] and decreased levels of 25(OH)D 3 in the serum [ 33 , 86 ] positively correlate with melanoma prevalence and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-melanoma activity of vitamin D derivatives have been reported previously [ 35 , 36 , 37 , 38 , 39 , 40 ]. In addition, the presence of specific polymorphisms of VDR [ 41 , 42 , 43 ] or a decreased expression of VDR , CYP27B1 , CYP24A1 and defects in vitamin D signaling are linked to more advanced stages of melanoma or poorer prognosis [ 44 , 45 , 46 , 47 , 48 ]. Furthermore, proper supplementation with vitamin D is believed to be an important factor in cancer prevention [ 47 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…VDR cistrome analyses suggested that altered expression of VDR in colon cancer changes actions of VDR, thus affecting patient outcome 58 . A recent study showed that VDR genetic traits can modulate VDR protein expression in excised human melanoma tissues, which might have implications for effects of vitamin D activity on melanoma cells 59 .…”
Section: Discussionmentioning
confidence: 99%
“…While a functional role of VDR gene polymorphisms has not yet been established, the association between Apa-I gene variant and MetS observed in the present study could be assumed to be linked to disturbed VDR gene expression [ 33 ]. The Apa-I polymorphism is located at the 3′ untranslated region (3′ UTR) of the VDR gene, which has been recognized as being involved in the modulation of gene expression, especially through the regulation of mRNA stability and efficiency of protein translation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%